2013
DOI: 10.1016/j.neuropharm.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based discovery of antagonists for GluN3-containing N-methyl-d-aspartate receptors

Abstract: NMDA receptors are ligand-gated ion channels that assemble into tetrameric receptor complexes composed of glycine-binding GluN1 and GluN3 subunits (GluN3A-B) and glutamate-binding GluN2 subunits (GluN2A-D). NMDA receptors can assemble as GluN1/N2 receptors and as GluN3-containing NMDA receptors, which are either glutamate/glycine-activated triheteromeric GluN1/N2/N3 receptors or glycine-activated diheteromeric GluN1/N3 receptors. The glycine-binding GluN1 and GluN3 subunits display strikingly different pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 46 publications
1
65
1
Order By: Relevance
“…At higher glycine concentrations, the selective block by TK40 at GluN1 subunits is outcompeted, resulting in diminished receptor current (declining phase), which is in agreement with previous reports (41,42). For glycine-activated responses at wild-type GluN1/N3 receptors, we have previously reported that only negligible current responses (Ͻ10 nA) are observed at GluN1/N3A receptors upon glycine application and that glycine concentrations above 10 M result in diminished receptor current at GluN1/N3B receptors, thereby producing a bell-shaped concentration-response relationship (38). Despite the potentiation, we still observed bell-shaped glycine concentration-response profiles at both wild-type GluN1/N3A and GluN1/N3B receptors in the presence of 3 M TK40, with the receptor current diminished at glycine concentrations above 100 M (Fig.…”
Section: Tk40supporting
confidence: 92%
See 4 more Smart Citations
“…At higher glycine concentrations, the selective block by TK40 at GluN1 subunits is outcompeted, resulting in diminished receptor current (declining phase), which is in agreement with previous reports (41,42). For glycine-activated responses at wild-type GluN1/N3 receptors, we have previously reported that only negligible current responses (Ͻ10 nA) are observed at GluN1/N3A receptors upon glycine application and that glycine concentrations above 10 M result in diminished receptor current at GluN1/N3B receptors, thereby producing a bell-shaped concentration-response relationship (38). Despite the potentiation, we still observed bell-shaped glycine concentration-response profiles at both wild-type GluN1/N3A and GluN1/N3B receptors in the presence of 3 M TK40, with the receptor current diminished at glycine concentrations above 100 M (Fig.…”
Section: Tk40supporting
confidence: 92%
“…We recently reported a virtual screen of GluN3A LBD that was based on three hybrid models of the GluN3A LBD in an antagonist-bound state (38). The models were virtually screened against a compound library of ϳ4 million commercially available compounds, of which 99 shortlisted compounds were obtained.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations